Solvent effects on the fluorescence and effective three-photon absorption of a Zn(II)-[meso-tetrakis(4-octyloxyphenyl)porphyrin]. (June 2018) - Wan, Yong; Xue, Yuxiong; Sheng, Ning; Rui, Guanghao; Lv, Changgui; He, Jun; Gu, Bing; Cui, Yiping
Highlights: Tunable effective three-photon absorption of Zn(II)-porphyrin by changing of solvents. Effective three-photon absorption cross-section increases as the solvent polarity decreases. Low polar solvents are beneficial to applications of Zn(II)-porphyrin in optical limiting. Abstract: The fluorescence and effective three-photon absorption (3PA) properties of Zn(II)-[meso-tetrakis(4-octyloxyphenyl)porphyrin] (labeled Zn(II)-porphyrin) dissolved in three different polar solvents were systematically investigated. The electrochemical and photophysical properties of Zn(II)-porphyrin were investigated by 1 H NMR spectra, IR spectra, mass spectroscopy, and electronic absorption spectra. The fluorescence emission of Zn(II)-porphyrin in three different solvents excited at the wavelengths of 420 nm (Soret band) and 550 nm (Q-band) were analyzed. By performing Z-scan experiments with femtosecond laser pulses at a wavelength of 800 nm, the effective 3PA process of Zn(II)-porphyrin in three different solvents was observed and the underlying mechanism was discussed in detail. It is found that the fluorescence spectra slightly depend on the polarity of the solvent. Interestingly, the effective 3PA properties of Zn(II)-porphyrin strongly depend on the solvent polarity. The lower the solvent polarity is, the larger effective 3PA cross-section is. Low polar solvents are beneficial to applications of Zn(II)-porphyrin in optical limiting, photodynamic therapy, etc.